Archival Literacy and Primary Source Literacy: A Collaborative Instructional Toolkit for Introductory Composition and Beyond⁠⁠⁠⁠⁠⁠⁠ - Leaman, Kristin; Harmeyer, Adriana (Archivaria)

(untitled) (Association of Canadian Archivists, 2025)
This article is a case study that addresses challenges archivists and introductory composition instructors can experience when working to embed archival and primary source literacy into a course and models how to successfully overcome related obstacles. Building on the excellent work of James Roussain, it employs the archivist-as-educator model not only to teach the students but also to train the disciplinary instructor. Teaching instructors archival and primary source literacy and training them how to teach these types of literacy enhances student success. Acknowledging the literature that discusses the ineffectiveness of one-shot guest lectures, the authors have designed and piloted an archival and primary source literacy toolkit that provides a scalable and effective model for embedding a module and assignment into an introductory composition course at a large research university. The inquiry-based active-learning activities in the toolkit are scaffolded to prepare students for the assignment. Furthermore, the toolkit provides guidance on how instructors and archivists can collaboratively develop the skills they need to successfully embed the module into introductory composition courses.